2014
DOI: 10.1108/apjba-05-2013-0046
|View full text |Cite
|
Sign up to set email alerts
|

The experience of New Zealand in the evolving wine markets of Japan and Singapore

Abstract: Purpose – The purpose of this paper is to explore the developing wine markets of Japan and Singapore for New Zealand (NZ) wine. It is principally an opinion piece with some reference to the academic literature, to the trade literature and quite a bit of the authors' own experiences as marketing academics conducting research in East Asia on the growth of wine drinking in this region of the globe. Design/methodology/approach – This paper i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Japanese market shares fluctuated until 2013, when a period of slow continuous growth began, resulting from consumption habit changes. The people began to view wine as a daily drink, and became increasingly curious about higher quality wines (Corsi et al, 2013), which generated an increase in sparkling wine consumption, especially among women (Rod and Beal, 2014). Germany, despite presenting a constant fall, starting with 11.5 points in 2004 and experiencing fluctuations between 2006 and 2011, continued to be a strong importer, due to having sparkling wine as an occasional celebratory beverage (Dressler, 2018).…”
Section: Market Share and Concentration Of Importsmentioning
confidence: 99%
See 1 more Smart Citation
“…Japanese market shares fluctuated until 2013, when a period of slow continuous growth began, resulting from consumption habit changes. The people began to view wine as a daily drink, and became increasingly curious about higher quality wines (Corsi et al, 2013), which generated an increase in sparkling wine consumption, especially among women (Rod and Beal, 2014). Germany, despite presenting a constant fall, starting with 11.5 points in 2004 and experiencing fluctuations between 2006 and 2011, continued to be a strong importer, due to having sparkling wine as an occasional celebratory beverage (Dressler, 2018).…”
Section: Market Share and Concentration Of Importsmentioning
confidence: 99%
“…Features: fluctuates between its lowest mark, 0.92 points, and its highest mark, 0.97; the results indicated France as the world's largest exporter of sparkling wines. (Rod and Beal, 2014). -Australia: The country's figures showed that, in the first year of the analysis, it was classified as a reexporter.…”
Section: Net Export Indexmentioning
confidence: 99%
“…Japanese wine preferences are influenced by demographics with differences due to age, income, region, consumption frequency, and total expenditures (Bruwer and Buller 2013). Rod and Beal (2014) note that wine is viewed as an iconic symbol of globalization in Japan and consumers tend to favor French wine due to its global standing. The same associations and preferences for French wine are apparent among Chinese wine consumers (Muhammad et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, Japanese wine consumption was 1.9 liters per capita but rose to 2.6 liters per capita in 2018. In Italy, for instance, consumption is 45 liters per capita (Rod and Beal 2014; Aoki and Negishi 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation